A study on partnering and strategic alliances in the shipping industry - Lim, Peng Juay. (2012)
The aim of this report is to study the topic on Partnering and Strategic Alliance in the Shipping Industry. Three sectors of the shipping industry will be covered in this report, namely the bulk (tanker), the liner as well as the offshore sectors. The report will first discuss the various reasons as to why shipping companies enter into alliances and move on to the different factors affecting the success or failure of such alliances. In the final part of the report, discussions will be drawn up for the future prospects of entering strategic alliances in the shipping industry. This is part of a three segment study which will emphasize on the Cost (Reasons for Alliances); Transparency and Mutual Trust (Success / Failure in Alliances); and the Future Drivers of partnering and alliances.